Application of SiO2 / C composite material in preparation of upper apex
The use of a SiO2/C composite material in tire upper apex rubber addresses the issues of aging and fatigue resistance by improving dispersibility and bonding, resulting in a more durable tire component.
Patent Information
- Application Number
- CN202411393286.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-08
AI Technical Summary
Existing upper apex rubber compositions in tires fail to simultaneously provide adequate aging resistance and fatigue resistance, especially under high temperatures, leading to premature fatigue fractures.
Application of a SiO2/C composite material prepared by combining carbonized edible fungus cultivation bodies with porous silica, which is mixed with natural rubber, activators, tackifying resin, and vulcanizing agents to form a rubber composition with improved dispersibility and bonding properties.
The SiO2/C composite material reduces heat generation and enhances fatigue resistance, offering a more durable upper apex rubber with better high-temperature performance.
Smart Images

Figure BDA0005073035610000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tire manufacturing, and in particular to application of a SiO2 / C composite material in preparing an upper apex rubber. Background Art
[0002] The function of the apex is to fill the space between the carcass wrapping part and the inner carcass around the toe. However, the carcass and the end of the wire wrap of the all-steel radial tire are located in the position with large movement inside the tire. These parts are prone to accidents, and the apex can prevent such accidents. The apex of most tires is divided into upper apex and lower apex. The upper apex absorbs energy, and the lower apex fixes the toe and the carcass, and together improves the overall rigidity of the toe. Tubeless filling rubber generally uses a single rubber compound, and inner tube filling rubber is generally divided into upper and lower apex. The upper apex of the inner tube bears the flexural deformation of the tire bead. The specific requirements of the upper apex are: fatigue resistance, lower hardness than the lower filling rubber, good viscosity of the semi-finished product, fast vulcanization speed, good dynamic performance, etc.
[0003] In order to meet the above functions, in addition to using rubber with excellent adhesion to the steel wire, the upper triangle rubber is also required to have a medium degree of hardness, a hard-soft transition, and a certain hardness and good flexibility. Therefore, this formula design focuses on solving four problems: 1. Flexion, 2. Heat generation, 3. High temperature fatigue, 4. Aging, and a long flat line. Solving these problems can effectively solve the problem of the hollow mouth.
[0004] The temperature of the upper triangle rubber during tire driving can usually reach 70-100℃. At this temperature, the modulus of the rubber will decrease. In order to improve the modulus and fatigue performance at high temperatures, the formula design usually adopts a high-sulfur and low-promoter system. The upper triangle prepared by this system has no fatigue problem, but it brings low aging retention rate, polysulfide bonds break to form single sulfur, and fatigue in the middle and late stages becomes worse, which leads to easy fatigue fracture.
[0005] As road conditions improve, tires are generally used for more than two years, which requires better high-temperature fatigue resistance. Therefore, developing upper triangle rubber with both aging resistance and fatigue resistance is a major challenge in the industry. Summary of the invention
[0006] In view of this, the present invention provides an application of a SiO2 / C composite material in the preparation of an upper apex rubber, so as to solve the problem that the existing upper apex rubber cannot simultaneously solve the aging resistance and fatigue resistance.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The invention discloses an application of a SiO2 / C composite material in preparing an upper apex rubber, wherein the upper apex rubber comprises the following components in parts by mass: 100 parts of natural rubber; 0 to 40 parts of filler; 10 to 60 parts of SiO2 / C composite material; 5 to 10 parts of activator; 0.5 to 4 parts of tackifying resin; 3 to 6 parts of vulcanizer; and 2 to 5 parts of antioxidant.
[0009] Preferably, the preparation method of the SiO2 / C composite material is as follows:
[0010] 1) mixing the edible fungus cultivation body with porous silica to obtain a silica composite edible fungus cultivation body;
[0011] The silicon dioxide composite edible fungus cultivation body is mixed with edible fungi to culture the edible fungi; after the culture is completed, the edible fungi are removed and the discarded cultivation body is retained;
[0012] 2) Carbonizing the waste culture medium in step 1 to obtain a SiO2 / C composite material.
[0013] Preferably, in step 1), the mass ratio of the porous silica to the edible fungus culture medium is 1:1-10; and the edible fungus culture time is ≥3 months.
[0014] Preferably, the carbonization temperature in step 2) is 600-950°C, the time is 10-60 min, and the rate of heating to the carbonization temperature is 5-15°C / min.
[0015] Preferably, the filler comprises carbon black and / or white carbon black.
[0016] Preferably, the activator comprises one or more of stearic acid, zinc oxide, zinc stearate and lignin zinc salt.
[0017] Preferably, the tackifying resin includes one or more of tackifying resin 203, tackifying resin 204 or petroleum tackifying resin C5.
[0018] Preferably, the vulcanizing agent comprises insoluble sulfur and / or a sulfur-containing accelerator.
[0019] Preferably, the antioxidant includes antioxidant 4020 and / or polytrimethyldihydroquinoline.
[0020] Preferably, the preparation method of the upper apex glue is as follows:
[0021] The natural rubber, filler, SiO2 / C composite material, activator, tackifying resin and antioxidant are first mixed to obtain a masterbatch; and the masterbatch and vulcanizing agent are second mixed to obtain an upper apex rubber.
[0022] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention creatively applies bio-based SiO2 / C composite materials to the preparation of tire upper apex rubber, which can effectively replace white carbon black or carbon black in the upper apex rubber. The upper apex rubber prepared by this method has low heat generation characteristics and fatigue resistance.
[0024] The SiO2 / C composite material described in the present invention is preferably a SiO2 / C aggregate formed by organically combining the carbonization of edible fungi with SiO2, which has high dispersibility and can reduce the Payne effect of the filler, thereby reducing heat generation; the SiO2 / C composite material prepared in the present invention is preferably prepared using porous silica material, which can form a tight bond with C, and the tight bond between the rubber segment and the filler is improved through the porosity of the SiO2 / C composite material, reducing the shedding of the rubber segment from the filler surface during fatigue, so that the prepared upper apex rubber composition has low hysteresis and excellent fatigue resistance.
[0025] The present invention creatively applies bio-based SiO2 / C composite materials to the preparation of tire upper apex rubber, which can effectively replace white carbon black or carbon black in the upper apex rubber. The upper apex rubber prepared by this method has low heat generation characteristics and fatigue resistance.
[0026] The SiO2 / C composite material described in the present invention is preferably a SiO2 / C aggregate formed by organically combining the carbonization of edible fungi with SiO2, which has high dispersibility and can reduce the Payne effect of the filler, thereby reducing heat generation. The present invention solves the problem of the application of white carbon black in the upper triangle formula. Usually, white carbon black is combined with rubber through chemical bonding of silane coupling agents. The chemical bonding breaks chemical bonds during fatigue to form a large number of initial cracks, resulting in poor tire durability, thereby limiting the application of white carbon black in the upper three-rubber formula to reduce heat generation.
[0027] The SiO2 / C composite material prepared in the present invention is preferably prepared using porous silica material, which can form a close bond with C. The porosity of the SiO2 / C composite material improves the close bond between the rubber segment and the filler, reduces the shedding of the rubber segment from the filler surface during fatigue, and makes the prepared upper apex rubber composition have low hysteresis and excellent fatigue resistance. DETAILED DESCRIPTION
[0028] The present invention provides an application of a SiO2 / C composite material in preparing an upper triangle rubber, wherein the upper triangle rubber comprises the following components in parts by mass: 100 parts of natural rubber, 0-40 parts of a filler, 10-60 parts of a SiO2 / C composite material, 5-10 parts of an activator, 0.5-4 parts of a tackifying resin, 3-6 parts of a vulcanizing agent, and 2-5 parts of an antioxidant; preferably, the composition comprises 100 parts of natural rubber, 1-30 parts of a filler, 20-50 parts of a SiO2 / C composite material, 6-9 parts of an activator, 1-3 parts of a tackifying resin, 4-5 parts of a vulcanizing agent, and 3-4 parts of an antioxidant; further preferably, the composition comprises 100 parts of natural rubber, 10-20 parts of a filler, 30-40 parts of a SiO2 / C composite material, 8 parts of an activator, 2 parts of a tackifying resin, 4.5 parts of a vulcanizing agent, and 3.5 parts of an antioxidant.
[0029] In the present invention, the preparation method of the SiO2 / C composite material is as follows:
[0030] 1) mixing the edible fungus cultivation body with porous silica to obtain a silica composite edible fungus cultivation body;
[0031] The silicon dioxide composite edible fungus cultivation body is mixed with edible fungi to culture the edible fungi; after the culture is completed, the edible fungi are removed and the discarded cultivation body is retained;
[0032] 2) Carbonizing the waste culture medium in step 1 to obtain a SiO2 / C composite material.
[0033] In the present invention, the mass ratio of the porous silica to the edible fungus culture medium in step 1) is 1:1-10, preferably 1:2-4, more preferably 1:2; the edible fungus culture time is ≥3 months, further preferably ≥3.5 months, more preferably 4 months.
[0034] In the present invention, the edible fungus culture medium in step 1) preferably includes a biomass carbon source, which includes but is not limited to one or more of cottonseed hulls, corn cobs, leaf and wood chips, bean straw powder, wheat straw powder, peanut shells, bran and rice bran.
[0035] In the present invention, the source of the edible fungus culture body in step 1) is not limited, and commercially available or non-commercially available products known to those skilled in the art can be used.
[0036] In the present invention, the porous silica in step 1) preferably includes one or more of silica lattice powder, carbon ore, diatomaceous earth, diatom shale, opal, zeolite and montmorillonite, and further preferably includes silica lattice powder, diatomaceous earth, diatom shale, opal, zeolite or montmorillonite, and more preferably silica lattice powder.
[0037] In the present invention, the grade of the carbon steel is preferably TSI-A5008.
[0038] In the present invention, the particle size of the porous silica in step 1) is preferably 500 nm to 100 μm, more preferably 500 nm to 50 μm, and more preferably 500 nm to 10 μm; the specific surface area is preferably 60 to 500 m 2 / g, more preferably 60 to 300 m 2 / g, more preferably 60 to 200 m 2 / g; the pore size is preferably 2 to 100 nm; the porosity is preferably 0.1 to 5 cm 3 / g, more preferably 0.1 to 3 cm 3 / g, more preferably 0.1 to 2 cm 3 / g.
[0039] In the present invention, the carbonization in step 2) is preferably carried out under a protective atmosphere; the protective atmosphere is preferably at least one of nitrogen or argon.
[0040] In the present invention, the carbonization temperature in step 2) is preferably 600-950°C, more preferably 700-900°C, and more preferably 800°C; the time is preferably 10-60 min, more preferably 30-60 min, and more preferably 60 min; the rate of heating to the desired carbonization temperature is preferably 5-15°C / min, more preferably 5-10°C / min, and more preferably 5°C / min.
[0041] In the present invention, the carbonization in step (2) preferably further comprises: crushing and screening in sequence.
[0042] In the present invention, the sieved particle size D50 is preferably 500 nm to 45 μm, more preferably 500 nm to 20 μm, and even more preferably 500 nm to 10 μm.
[0043] In the present invention, waste edible fungus culture bodies are used as carbon sources and fermented. At the same time, micron-sized silicon dioxide particles containing abundant nanopores are introduced when preparing the edible fungus culture bodies. The porous structure can provide a large number of attachment sites for the uniform attachment of fungi microorganisms, and provide a good temperature and humidity growth environment for fungi microorganisms, which is conducive to the rapid growth of fungi microorganisms. Since fungi microorganisms exchange organic matter with the surrounding edible fungus culture bodies during growth, the starch, polysaccharides, proteins, esters and other components in the edible fungus culture bodies are effectively utilized, so that the porous structure of fungi microorganisms and silicon dioxide forms a microscopic, mesoscopic and macroscopic three-dimensional mycelial structure, which provides a large number of attachment sites for the dispersion of biomass carbon on SiO2, helps to form a molecular-level biomass carbon structure distribution, and realizes the organic combination of biomass carbon and porous SiO2. After picking mature edible fungi, the discarded silica composite edible fungi culture is carbonized to promote the dehydration and condensation of the biomass carbon structure in the culture, remove the internal hydrogen and oxygen elements, and form nanoscale holes at the original position, forming a SiO2 / C composite material with good structural properties. Therefore, the biomass carbon source in the silica composite edible fungi culture forms a natural microscopic porous structure after multiple interactions with the microbial flora, and can become the best source for constructing an ideal SiO2 / C composite material after being compounded with SiO2 and fermented again.
[0044] The SiO2 in the preparation method of the present invention is derived from minerals, and the carbon is derived from biomass. Compared with the method in which the carbon source is derived from petroleum and chemical organic synthesis, it is more environmentally friendly and effectively utilizes the discarded edible fungus cultivation body, solves the problems of high energy consumption and environmental unfriendliness in the preparation process of the prior art, and realizes the green preparation of SiO2 / C composite materials.
[0045] The present invention can make up for the lack of biomass silicon in the edible fungus cultivation body by adding different proportions of micron-sized porous silicon dioxide into the edible fungus cultivation body, while achieving controllable ratio of carbon to silicon dioxide in the SiO2 / C composite material.
[0046] The present invention carbonizes the biomass carbon source of the three-dimensional mycelium structure attached to the SiO2 porous site, and the obtained SiO2 / C composite material has the characteristics of uniform distribution of SiO2 phase and biomass carbon phase, is not easy to agglomerate, has good dispersibility, and is suitable for use as a rubber functional filler. At the same time, the prepared SiO2 / C composite material has good low heat generation performance when used as a rubber filler.
[0047] In the present invention, the filler includes carbon black and / or white carbon black.
[0048] In the present invention, the carbon black includes one or more of N375, N330, N326, N660 and pyrolysis carbon black.
[0049] In the present invention, the activator includes one or more of stearic acid, zinc oxide, zinc stearate and lignin zinc salt.
[0050] In the present invention, the tackifying resin includes one or more of tackifying resin 203, tackifying resin 204 or petroleum tackifying resin C5.
[0051] In the present invention, the vulcanizing agent includes insoluble sulfur and / or a sulfur-containing accelerator.
[0052] In the present invention, the antioxidant includes antioxidant 4020 and / or polytrimethyldihydroquinoline (antioxidant RD).
[0053] In the present invention, the preparation method of the upper apex glue is as follows:
[0054] The natural rubber, filler, SiO2 / C composite material, activator, tackifying resin and antioxidant are first mixed to obtain a masterbatch; and the masterbatch and vulcanizing agent are second mixed to obtain an upper apex rubber.
[0055] In the present invention, the first mixing is specifically: setting the mixing speed to 45-55rpm, adding each component, mixing for 30-50 seconds, lifting the bolt and pressing the bolt to mix for 20-30 seconds, lifting the bolt and pressing the bolt to mix to 145-165°C for rubber removal, and obtaining a masterbatch; the mixing speed can be specifically 46rpm, 48rpm, 50rpm, 52rpm, 54rpm; the mixing time can be specifically 32 seconds, 35 seconds, 38 seconds, 40 seconds, 42 seconds, 45 seconds, 48 seconds; the mixing time of lifting the bolt and pressing the bolt can be specifically 22 seconds, 24 seconds, 25 seconds, 26 seconds, 28 seconds; the mixing temperature of lifting the bolt and pressing the bolt can be specifically 146°C, 148°C, 150°C, 152°C, 155°C, 158°C, 160°C, 162°C, 164°C.
[0056] In the present invention, the second mixing is specifically: setting the rotation speed to 25-35rpm, adding each component, mixing for 30-50 seconds, lifting the bolt and pressing the bolt to mix for 20-30 seconds, lifting the bolt and pressing the bolt to mix to 95-110°C for rubber removal, and obtaining a fatigue-resistant rubber composition; the mixing speed can be specifically 26rpm, 28rpm, 30rpm, 32rpm, 34rpm; the mixing time can be specifically 32 seconds, 35 seconds, 38 seconds, 40 seconds, 42 seconds, 45 seconds, 48 seconds; the mixing time for lifting the bolt and pressing the bolt can be specifically 22 seconds, 24 seconds, 25 seconds, 26 seconds, 28 seconds; the mixing temperature for lifting the bolt and pressing the bolt can be specifically 96°C, 98°C, 100°C, 102°C, 105°C, 108°C.
[0057] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0058] Example 1
[0059] 2 kg of Auricularia auricula culture (from the Science and Technology Demonstration Park of Dongjingcheng Forestry Bureau, Heilongjiang) and 500 g of Silica powder (D50-8 μm, model TSI-1, manufactured by Harbin Silica New Materials Co., Ltd., with a particle size of 500 nm to 10 μm and a specific surface area of 60 to 200 m 2 / g, pore size is 2~100nm, porosity is 0.1~2cm 3 / g) and evenly mixed to obtain a silicon dioxide composite edible fungus culture body;
[0060] After sterilizing the silica composite edible fungus culture body at 120° C. for 1.5 h, inoculating the auricularia auricula into the silica composite edible fungus culture body for cultivation, and after the auricularia auricula has been cultivated for 4 months, removing the mature auricularia auricula and retaining the discarded culture body;
[0061] The discarded culture medium was naturally dried for 24 hours, and then placed in a carbonization furnace, and heated to 700°C at a heating rate of 5°C / min under nitrogen protection for carbonization for 30 minutes; the obtained silicon-carbon composite was ball-milled in a planetary ball mill at 500 rpm for 30 minutes, and then the ball-milled sample was sieved by a centrifugal classifier to obtain a sample with a particle size D50≤5μm, to obtain a SiO2 / C composite material.
[0062] Start the internal mixer, set the speed to 50rpm, add 100 parts of natural rubber, 45 parts of SiO2 / C composite material, 6 parts of activator (2 parts of stearic acid, 4 parts of zinc oxide), 2032 parts of tackifying resin, 40202.5 parts of antioxidant; mix for 35 seconds, remove the bolt and press the bolt to mix for 20 seconds, remove the bolt and press the bolt to mix until 152℃ to discharge the glue, and obtain the masterbatch;
[0063] Start the internal mixer, set the speed to 30 rpm, add masterbatch, insoluble sulfur and sulfur-containing accelerator TBBS (the mass ratio of natural rubber to insoluble sulfur and sulfur-containing accelerator (TBBS) in the masterbatch is 100:3.14:1), mix for 30 seconds, remove the bolt and press the bolt to mix for 20 seconds, remove the bolt and press the bolt to mix until 105°C to discharge the glue, and obtain the upper apex rubber.
[0064] Example 2
[0065] The preparation of SiO2 / C composite material is the same as in Example 1.
[0066] Start the internal mixer, set the speed to 50rpm, add 100 parts of natural rubber, 15 parts of white carbon black GR175, 30 parts of SiO2 / C composite material, 9.5 parts of activator (3.5 parts of stearic acid, 6 parts of zinc oxide), 52 parts of petroleum tackifying resin C, and 2.5 parts of antioxidant RD; mix for 35 seconds, remove the plug and press the plug to mix for 20 seconds, remove the plug and press the plug to mix until the glue is discharged at 152℃ to obtain a masterbatch;
[0067] Start the internal mixer, set the speed to 30 rpm, add masterbatch, insoluble sulfur and sulfur-containing accelerator TBBS (the mass ratio of natural rubber to insoluble sulfur and sulfur-containing accelerator (TBBS) in the masterbatch is 100:3.14:1), mix for 30 seconds, remove the bolt and press the bolt to mix for 20 seconds, remove the bolt and press the bolt to mix until 105°C to discharge the glue, and obtain the upper apex rubber.
[0068] Example 3
[0069] The preparation of SiO2 / C composite material is the same as in Example 1.
[0070] Start the internal mixer, set the speed to 55 rpm, add 100 parts of natural rubber, 10 parts of carbon black N326, 35 parts of SiO2 / C composite material, 8 parts of activator (2 parts of stearic acid, 6 parts of zinc oxide), 3 parts of petroleum tackifying resin C5, and 40202 parts of antioxidant; mix for 30 seconds, remove the bolt and press the bolt to mix for 25 seconds, remove the bolt and press the bolt to mix until the glue is discharged at 152°C to obtain a masterbatch;
[0071] Start the internal mixer, set the speed to 25 rpm, add masterbatch, insoluble sulfur and sulfur-containing accelerator TBBS (the mass ratio of natural rubber to insoluble sulfur and sulfur-containing accelerator (TBBS) in the masterbatch is 100:3:2), mix for 35 seconds, remove the bolt and press the bolt to mix for 25 seconds, remove the bolt and press the bolt to mix until 100°C to discharge the glue, and obtain the upper apex rubber.
[0072] Example 4
[0073] The preparation of SiO2 / C composite material is the same as in Example 1.
[0074] Start the internal mixer, set the speed to 55 rpm, add 100 parts of natural rubber, 640 parts of carbon black N32, 10 parts of SiO2 / C composite material, 5 parts of activator (3 parts of stearic acid, 2 parts of zinc oxide), 2030.5 parts of tackifying resin, and 40204 parts of antioxidant; mix for 40 seconds, remove the bolt and press the bolt to mix for 20 seconds, remove the bolt and press the bolt to mix until the glue is discharged at 150°C to obtain a masterbatch;
[0075] Start the internal mixer, set the speed to 35 rpm, add masterbatch, insoluble sulfur and sulfur-containing accelerator TBBS (the mass ratio of natural rubber to insoluble sulfur and sulfur-containing accelerator (TBBS) in the masterbatch is 100:2:1), mix for 40 seconds, remove the bolt and press the bolt to mix for 30 seconds, remove the bolt and press the bolt to mix until the temperature is 95°C and the rubber is discharged to obtain the upper apex rubber.
[0076] Example 5
[0077] 2 kg of Auricularia auricula culture (from the Science and Technology Demonstration Park of Dongjingcheng Forestry Bureau, Heilongjiang) and 1 kg of Silica powder (D50-8 μm, model TSI-1, manufactured by Harbin Silica New Materials Co., Ltd., with a particle size of 500 nm to 10 μm and a specific surface area of 60 to 200 m 2 / g, pore size is 2~100nm, porosity is 0.1~2cm 3 / g) and evenly mixed to obtain a silicon dioxide composite edible fungus culture body;
[0078] After sterilizing the silica composite edible fungus culture body at 120° C. for 1.5 h, inoculating the auricularia auricula into the silica composite edible fungus culture body for cultivation, and after the auricularia auricula has been cultivated for 3 months, removing the mature auricularia auricula and retaining the discarded culture body;
[0079] The discarded culture medium was naturally dried for 24 hours, and then placed in a carbonization furnace, heated to 950°C at a heating rate of 10°C / min under nitrogen protection and carbonized for 60 minutes; the obtained silicon-carbon composite was ball-milled in a planetary ball mill at 500 rpm for 30 minutes, and then the ball-milled sample was sieved by a centrifugal classifier to obtain a sample with a particle size D50≤3μm, to obtain a SiO2 / C composite material.
[0080] Start the internal mixer, set the speed to 45 rpm, add 100 parts of natural rubber, 60 parts of SiO2 / C composite material, 9 parts of activator (5 parts of stearic acid, 4 parts of zinc oxide), 2034 parts of tackifying resin, and 40205 parts of antioxidant; mix for 50 seconds, remove the plug and press the plug to mix for 20 seconds, remove the plug and press the plug to mix until the glue is discharged at 145°C to obtain a masterbatch;
[0081] Start the internal mixer, set the speed to 30 rpm, add masterbatch, insoluble sulfur and sulfur-containing accelerator TBBS (the mass ratio of natural rubber to insoluble sulfur and sulfur-containing accelerator (TBBS) in the masterbatch is 100:3.5:1), mix for 30 seconds, remove the bolt and press the bolt to mix for 25 seconds, remove the bolt and press the bolt to mix until 105°C to discharge the glue, and obtain the upper apex rubber.
[0082] Comparative Example 1
[0083] The difference between this comparative example and Example 1 is that an equal mass fraction of carbon black N326 is used to replace the SiO2 / C composite material.
[0084] Comparative Example 2
[0085] The difference between this comparative example and Example 2 is that an equal mass fraction of carbon black N326 is used to replace the SiO2 / C composite material.
[0086] Experimental Example 1
[0087] The relevant properties of Examples 1-2 and Comparative Examples 1-2 were tested, and the test results are shown in Table 1.
[0088] M300, TB, EB% testing method: tensile properties in accordance with GB / T528-1998.
[0089] Tanδ / 60℃ is tested by DMA, DMA test conditions: 151℃×30min (test condition frequency 20Hz, strain 10±2%, temperature scan 0~80℃)
[0090] High temperature fatigue (aging) test conditions: 100°C, elongation 1.8%, test speed 150CPM.
[0091] Table 1 Test results of relevant properties of apex glue
[0092]
[0093] It can be seen from the above comparative examples 1, 2 and examples 1 to 5 that the reinforcing effect of the SiO2 / C composite material prepared in the experiment is similar to that of white carbon black and N326. The heat generation of the SiO2 / C composite material is 35.5% lower (= (0.135-0.087) / 0.135), and the fatigue resistance is improved by more than 50%. It can be seen from the above examples that the rubber composition prepared by using the SiO2 / C composite material has low heat generation performance and good fatigue resistance.
[0094] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0095] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An application of SiO2 / C composite material in the preparation of upper apex plastic, characterized in that: The upper triangle rubber comprises the following components in parts by mass: 100 parts of natural rubber; 0-40 parts of filler; 10-60 parts of SiO2 / C composite material; 5-10 parts of activator; 0.5-4 parts of tackifying resin; 3-6 parts of vulcanizer; and 2-5 parts of antioxidant.
2. The use of a SiO2 / C composite material according to claim 1 in preparing an upper apex, characterized in that: The preparation method of the SiO2 / C composite material is as follows: 1) mixing the edible fungus cultivation body with porous silica to obtain a silica composite edible fungus cultivation body; The silicon dioxide composite edible fungus cultivation body is mixed with edible fungi to culture the edible fungi; after the culture is completed, the edible fungi are removed and the discarded cultivation body is retained; 2) Carbonizing the waste culture medium in step 1 to obtain a SiO2 / C composite material.
3. The use of a SiO2 / C composite material according to claim 2 in the preparation of an upper apex plastic, characterized in that: The mass ratio of the porous silica to the edible fungus culture medium in step 1) is 1:1-10; the edible fungus culture time is ≥3 months.
4. The use of a SiO2 / C composite material in the preparation of an upper apex according to claim 3, characterized in that: The carbonization temperature in step 2) is 600-950°C, the time is 10-60 min, and the rate of heating to the carbonization temperature is 5-15°C / min.
5. Use of a SiO2 / C composite material according to any one of claims 1 to 4 in the preparation of an upper apex, characterized in that: The filler includes carbon black and / or white carbon black.
6. The use of a SiO2 / C composite material in the preparation of an upper apex according to claim 5, characterized in that: The activator comprises one or more of stearic acid, zinc oxide, zinc stearate and lignin zinc salt.
7. The use of a SiO2 / C composite material in the preparation of an upper apex according to claim 6, characterized in that: The tackifying resin includes one or more of tackifying resin 203, tackifying resin 204 or petroleum tackifying resin C5.
8. Use of a SiO2 / C composite material according to claim 6 or 7 in preparing an upper apex, characterized in that: The vulcanizing agent includes insoluble sulfur and / or a sulfur-containing accelerator.
9. The use of a SiO2 / C composite material according to claim 8 in preparing an upper apex, characterized in that: The antioxidant includes antioxidant 4020 and / or polytrimethyldihydroquinoline.
10. The use of a SiO2 / C composite material according to claim 9 in preparing an upper apex, characterized in that: The preparation method of the upper apex glue is as follows: The natural rubber, filler, SiO2 / C composite material, activator, tackifying resin and antioxidant are first mixed to obtain a masterbatch; and the masterbatch and vulcanizing agent are second mixed to obtain an upper apex rubber.
Citation Information
Patent Citations
waterproofing tarpaulin.
GR17515B
Carbon-coated white carbon black
CN103937293A
Modified white carbon black and tread rubber thereof
CN110396226A
Bio-based compound modified white carbon black, preparation method thereof and application of bio-based compound modified white carbon black in tire production
CN117757143A
Tire rubber composition comprising silica / carbon complex
KR1020100031418A
Cited By
High-temperature-resistant rubber composition, high-temperature-resistant upper apex and preparation method thereof
CN120842704A